PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENINGKATAN PENGETAHUAN DAN SIKAP TENTANG PENCEGAHAN COVID-19 DI DESA TIOUW KECAMATAN SAPARUA - Julen Evans Talakua; Dwight Nusawakan; Kreshas J.A Noija (Pasapua Health Journal, 2021)
Introduction: Indonesia’s condition during the current Covid-19 pandemic has shaken both inside and outside society, because the current pandemic has limited all activities, be it health education or the community. Corona virus is a virus that attacks the respiratory tract and causes high fever, cough, flu, shortness of breath and sore throat. Prevention measures in the community are to maintain hand hygiene by using a hand sanitizer or washing hands with soap and running water, avoiding touching parts of the face (such as the eyes, nose and mouth), applying coughing and sneezing ethics, wearing a mask and maintaining distance (at least 1 meters) from others. The purpose of this study was to determine the effect of health education on increasing knowledge and attitudes about preventing Covid19 in Tiouw Village, Saparua District. Method: The research method used is quantitative with a Pre- Experimental. The research sample was taken using a purposive sampling technique with a total sample of 93 respondents. Bivariate analysis using the Wilcoxon test. Results: the results of this study obtained were that some of the people of Tiouw Village with the knowledge level of the prior category were 39 (41.9%) and the knowledge category after was 54 (58.1%). Meanwhile, the attitude before conducting health education was 33 (41.9%) and the attitude after 60 (64.5%). There is an effect of Health Education on increasing knowledge and attitudes about preventing Covid-19 with the result (p <0.05). Conclusion: that there is an influence of Health Education on increasing knowledge and attitudes about preventing Covid-19 in Tiouw Village, Saparua District.